Revealing Expression Through Taboo Words in The Novel Peepshow - Arief Nugraha; Waladdin Panggabean; Adi Prautomo (Faculty of Letters Universitas Balikpapan, 2020)
The focuses of this research are to find out the forms of taboo words in the novel Peepshow and to explain how the expression through taboo words revealed in the novel Peepshow. The theory used in this research is Batistella’s theory of taboo words and expression theory according to Ekman’s theory of expression. The methodology employed is descriptive qualitative research in which the researcher tried to present the issues descriptively. As for the data, they were collected from the excerpt of the novel’s quotation. The researcher finds that the forms of taboo words in the novel Peepshow is Obscenity divided into. The use of impolite words in Body excretion and the use of impolite words in sexual function, Vulgarity divided into. The use of the impolite words in body anatomy and the use of the impolite words in sexual function. Profanity in the use of impolite words in religious cursing, and. The epithet in the use of impolite words by people’s status. While the researcher founds the revealing expression through the taboo words consisted of sad, angry, fear, happy, surprise, and disgust expression through obscenity, vulgarity, profanity, and epithet expression.